2002
DOI: 10.1006/viro.2001.1213
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy of Respiratory Syncytial Virus in African Green Monkeys by Intranasally Administered 2-5A Antisense

Abstract: Respiratory syncytial virus (RSV) is a leading cause of respiratory disease in infants, young children, immunocompromised patients, and the institutionalized elderly. Previous work had shown that RNase L, an antiviral enzyme of the interferon system, could be recruited to cleave RSV genomic RNA by attaching tetrameric 2prime prime or minute-5prime prime or minute-linked oligoadenylates (2-5A) to an oligonucleotide complementary to repetitive gene-start sequences within the RSV genome (2-5A antisense). A 2prime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…In addition, expression of RNase L inhibitor (RLI) suppressed the IFN-␥ effect against RSV. The potential of RNase L activator drugs to block RSV infections was demonstrated by targeting RSV genomic RNA with 2-5A linked to an antisense oligonucleotide against the RSV repetitive-gene start site (60). The 2-5A antisense drug administered by the intranasal route to RSV-infected African green monkeys reduced viral yields by 4-log 10 units.…”
Section: Rna Virusesmentioning
confidence: 99%
“…In addition, expression of RNase L inhibitor (RLI) suppressed the IFN-␥ effect against RSV. The potential of RNase L activator drugs to block RSV infections was demonstrated by targeting RSV genomic RNA with 2-5A linked to an antisense oligonucleotide against the RSV repetitive-gene start site (60). The 2-5A antisense drug administered by the intranasal route to RSV-infected African green monkeys reduced viral yields by 4-log 10 units.…”
Section: Rna Virusesmentioning
confidence: 99%
“…Specific cleavage of hRSV genome RNA has been detected at antisense oligonucleotide binding sites (184). Because of the pattern of RNA cleavage observed, it was suggested that endogenous RNase H participated in hRSV (2) and, more recently, in vivo using an African green monkey model of hRSV infection (230). As of this writing, there are no publications describing antisense therapy in human clinical trials.…”
Section: Therapy For Hrsv Diseasementioning
confidence: 99%
“…RNase L is a ribonuclease activated by 2 0 -5 0 -linked oligoadenylates generated in response to interferon activation. Linkage of 2 0 -5 0 oligoadenylate to an antisense oligonucleotide has been reported to promote selective cleavage of the targeted mRNA (Torrence et al, 1993;Leaman et al, 2002).…”
Section: Antisense Mechanism Of Actionmentioning
confidence: 99%